(untitled) (Journal of Social Sciences Review, 2023)
Wrongful convictions are a pervasive problem in Pakistan’s criminal justice system, leaving victims without adequate redress for the injustices they have suffered which inevitably undermines the credibility of the country’s criminal justice system. The objectives of the study at hand were to identify the key features of compensation frameworks, their effectiveness to redress the harms of wrongfully convicted persons and to recommend some appropriate legislative designs in the context of the criminal justice system in Pakistan. The qualitative research methodology was adopted and a comparative analysis of compensatory statutes of the US and UK has been taken into consideration. This study not only contributes to the literature on wrongful convictions and compensation but is also momentous for policymakers and legal practitioners, other stakeholders in Pakistan and other jurisdictions grappling with this issue. This study concludes streamlined monetary compensation, counseling and support services to redress the harms that are caused to innocent persons due to wrongful convictions. Additionally, the compensation process for wrongful convictions should be easily accessible, timely, and non-adversarial.